Transformasi strategis sistem informasi keperawatan di rumah sakit X menuju smart garden hospital - Wea, Maria Eka Brigida Wonga; Septirini, Maria Indah; Suhani, Nini; Perdana, Riska Rusfita; Septianata, Viesca; Hariyati, Roro Tutik Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: A smart garden hospital is an approach that prioritizes not only smart technology but also environmental sustainability, patient comfort, humanization of services, and operational efficiency based on information technology. Information and communication technology supports evidence-based nursing practice, strengthens patient safety, and meets global healthcare standards. Purpose: To describe the strategic transformation of X hospital nursing information system toward a smart garden hospital. Method: The field study used a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis approach. Data were analyzed using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, and mapped onto an Internal-External (IE) matrix to determine the organization's strategic position. Results: The analysis yielded an IFE score of 2.61 and an EFE score of 3.15, placing Hospital X in the